Literature Review on the Effectiveness of Risk Management Systems on Financial Performance in a Public Setting - Wadesango, Newman; Mhaka, Charity; Shava, Faith; Wadesango, Ongayi (Allied Business Academies, 2021)
The Parliamentary Accounting Committee (PAC) revealed that fraud cases had been prevalent in government departments including the Ministry of Higher and Tertiary Education, Science and Technology Development (MHTESTD). The Committee noted fraud cases through recurring audit findings such as funds embezzlement, dummy receipting, unauthorized and unsupported expenditure, flouting tender procedures, mismanagement of funds and management over rides by those charged with governance. The Auditor General (AG) of 2015 also reported that out of unsupported payments incurred were losses ranging from USD$ 3 million to USD$ 3.5 million. Innovation and Commercialization Fund (ICF) lost amount of USD$ 2.5 million owed to debtors through borrowings. However, National Education Training Fund lost USD$ 3.5 million to acquit Cadetship grants. AG’s report of 2015 observed that Ministry of Higher and Tertiary Education lost about USD$ 1.8 million to dummy receipting in polytechnics and teacher’s college. Analysis of AG report by ZIMCODD highlighted that inadequate risk based audit has negatively affected the financial performance of ministries as there is no audit committee for risk identification, assessment and monitoring in taking up risk management task thus IAF has been inefficient in accomplishing its audit plan, hence audit recurring perpetuated fraud activities.